Curriculum Evaluation of Major in Tourism Engineering Offered by The Amazon State University - Coromoto Marin, Haideé (2018)
Any curriculum must be continuously evaluating to be successful and of high quality in order to improve and achieve the full student´s formation. In fact, it becomes so important because it allows generating and obtaining significant achievements in the educational process towards a rational development and scientifically valid to face the current challenges. The aim of this research was to conduct the evaluation of the curriculum of Tourisms in the Amazon State University (UEA), through a methodology with a change-oriented epistemological approach. A participatory action research method was used, which consists of a systemic process where the participation of all actors involved in the educative process are required, even internal or external ones, because they have the deepest knowledge of their problems and reality. The results of the research shows the findings, failures, weaknesses and strengths as a base to solve them and promote the teaching quality which is one of the major educational challenges in the XXI century.